Delivering Comprehensive Social Services during a Pandemic: Experience of a New York City Student-Run Free Clinic - Dias, Jennifer; Lui, Madeline; Goldberger, Cody; Stewart, O’Jay; Deeb, Stephanie; Orozco Scott, Paloma; Berger, Natalie; Hughes, Terence; Weiss, Kevin; Carter, James; Pan, Jonathan; Paul, Megan; et al. (Journal of Student-Run Clinics, 2022)
Background: We describe the implementation of a remote operational model to provide targeted, multi-faceted social services during the coronavirus disease 2019 (COVID-19) pandemic at the East Harlem Health Outreach Partnership (EHHOP), a student-run, physician-supervised free clinic (SRFC) that serves uninsurable residents of East Harlem in New York City (NYC). The model attempts to mitigate the economic consequences of the pandemic while also safely meeting the needs of patients who were quarantined or otherwise medically vulnerable. Methods: We outline a step-by-step approach required to transition social services to a remote model, across six key workflows: (1) student volunteer recruitment, (2) fundraising, (3) grocery and financial grant allocation, (4) medication delivery, (5) mask delivery and patient education, and (6) broader community engagement. Results: Within 20 days of the first known case of COVID-19 in NYC, we established a protocol for remote care and expanded social services. From March to July 2020, EHHOP volunteers made 221 medication and 172 mask kit no-contact deliveries. To address food and housing insecurity, 140 patients were provided financial grants and an additional 109 received food deliveries. This comprehensive response was supported through emergency fundraising efforts that generated 66,690. Conclusions: By focusing on support for basic needs including food, medication, personal protective equipment, and patient education, EHHOP was able to bolster the safety-net for marginalized patients otherwise excluded from national economic recovery efforts and ensure continuous care for patients with chronic medical illness. EHHOP’s operational model for safe, remote delivery of social services provides other clinics with a framework to guide current and future emergency responses.